Predicting body compositions of live finishing pigs based on bioelectrical impedance analysis - Ji Seon An (Journal of Animal Science and Technology, 2021)
The objective of this study was to predict body compositions of live pigs using bioelectrical impedance procedures. In experiment 1, 32 crossbred (Duroc × Landrace × Yorkshire) finishing pigs with an average weight at 84.06 kg were used. In experiment 2, 96 crossbred (Duroc × Landrace × Yorkshire) finishing pigs with an average weight at 88.8 kg were used. A four-terminal body composition analyser was utilized to determine fat percentage. Lean meat percentage and backfat thickness were measured with a lean meat measuring meter. In experiment 1, fat percentage was not significantly correlated with lean meat percentage, although a tendency (p < 0.1) of a negative correlation was found. Backfat thickness was significantly correlated with fat percentage and lean meat percentage (r = 0.745 and r = −0.961, respectively). Coefficients of determination for fat percentage with lean meat percentage, fat percentage with backfat thickness, and backfat thickness with lean meat percentage were 0.503, 0.566, and 0.923, respectively. In experiment 2, fat percentage was significantly correlated with lean meat percentage (r = −0.972). Backfat thickness was also significantly correlated with fat percentage and lean meat percentage (r = 0.935 and r = −0.957, respectively). Results of this study indicate that bioelectrical impedance analysis might be useful for predicting body compositions of live finishing pigs.